Two new species of Atrichopogon Kieffer from Rio de Janeiro, Brazil (Diptera: Ceratopogonidae) - Felippe-Bauer, Maria Luiza; Da Silva, Tiago Do Nascimento; Alves, João Ricardo Carreira (Zootaxa, 2012)
Two new species of Atrichopogon, A. dactilus Felippe-Bauer and A. cavus Felippe-Bauer are described and illustrated based on male and female specimens from the southeast region of Brazil. The new species are compared with the other eight species of Neotropical Atrichopogon with distinctively pigmented wings and a key to the males of the species is provided.